1988
DOI: 10.1021/ja00233a006
|View full text |Cite
|
Sign up to set email alerts
|

Matrix isolation infrared studies of nucleic acid constituents. 5. Experimental matrix-isolation and theoretical ab initio SCF molecular orbital studies of the infrared spectra of cytosine monomers

Abstract: 2 Ec + AH* for temperatures below rollover and E,,, = Ec for temperatures above rollover.The selectivity for the hydrogenolysis of n-butane on the two surfaces has been identified with the occurrence of particular, adsorbed reaction intermediates on each surface. When our results are compared to those reported previously on supported iridium catalysts of varying metallic particle size,22 a direct correlation Registry No. C2H6,, C4Hlo,Supplementary Material Available: Details of mechanistic modeling of the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
250
0
5

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(273 citation statements)
references
References 3 publications
18
250
0
5
Order By: Relevance
“…27 To prevent any insidious effect such as decomposition of the cytosine molecule by the Pt surface in the present experiment, a 3-layer film of Ar was systematically used as a spacer. 39 Since, it is generally accepted from VUV, 40 photoelectron, 41 IR, 42 and Raman 42 spectroscopy studies that cytosine does not decompose upon heating up to 220°C in vacuum; the present sublimation temperature is expected to preserve the integrity of the molecule. After several days of experiments, the sample holder and the electron spectrometer needed to be heated at about 50°C during 48 hours in order to remove the insulating deposits that deteriorate the measurements.…”
Section: Methodsmentioning
confidence: 99%
“…27 To prevent any insidious effect such as decomposition of the cytosine molecule by the Pt surface in the present experiment, a 3-layer film of Ar was systematically used as a spacer. 39 Since, it is generally accepted from VUV, 40 photoelectron, 41 IR, 42 and Raman 42 spectroscopy studies that cytosine does not decompose upon heating up to 220°C in vacuum; the present sublimation temperature is expected to preserve the integrity of the molecule. After several days of experiments, the sample holder and the electron spectrometer needed to be heated at about 50°C during 48 hours in order to remove the insulating deposits that deteriorate the measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The origin of this confusion is almost certainly due to multiple tautomers present in the molecular beam. Microwave 80 and high resolution IR 81,82 spectroscopies reveal that there are (at least) three tautomers of Cyt present within a molecular beam. These are the biological keto tautomer, and the nonbiological enol and imino tautomers, which are present in a ratio of approximately 4:4:1, respectively (from microwave experiments).…”
Section: Dtmp -mentioning
confidence: 99%
“…The keto form is the biologically important one, with Watson-Crick base pairing in DNA, and predominant in solution. In matrix isolation Szczesniak et al observed both keto and enol forms with higher abundances for the latter and small contributions from the imino form 79 82 . They conclude that the deactivation pathways are quite different for the different tautomers, with three time constants for keto-cytosine and two for the others.…”
Section: Tautomersmentioning
confidence: 99%